Government Capability In Drug Control In East Kotawaringin Regency From The Dynamic Governance Perspective - Bimantara Nur Alim (Department of Public Administration, Muhammadiyah University of Makassar, 2022)
AbstractBased on the rapid development and environmental conditions, the drug problems in East Kotawaringin Regency are serious issues that must be resolved. The study aims to describe the government's capability in preventing drugs in the East Kotawaringin regency in terms of a dynamic governance perspective as well as to fill the gap since there are not many scholarly works on this study specifically at the local level. This research uses a qualitative method with a descriptive research type. The research was conducted in East Kotawaringin Regency with data collection techniques sourced from primary data in the form of in-depth interviews with the Head of the Narcotics Investigation Unit and the Secretariat of the Regency Narcotics Agency, then secondary data in the form of official reports and scientific articles. Data analysis techniques used in this research are data reduction, data presentation, and conclusion. The results of the study indicate that there is a capability improvement effort, but it is still not running optimally. The elements of thinking ahead and thinking again need more attention. Constraints faced are the lack of human resources and budgeting, the role of inter-agency is not coordinated in a structured manner, and the absence of a definitive agency, namely the Regency National Narcotics Agency, which also has a major influence on operational implementation. Meanwhile, the element of thinking across can be understood by the ranks of the local government with the efforts for comparative studies.AbstrakBerdasarkan perkembangan dan kondisi lingkungan yang cepat berubah, permasalahan narkoba di Kabupaten Kotawaringin Timur telah menjadi isu serius yang harus di selesaikan. Tujuan penelitian yaitu untuk menggambarkan kapabilitas pemerintah dalam pencegahan narkoba di kabupaten Kotawaringin Timur ditinjau dari perspektif dynamic governance sebagaimana untuk mengisi gap karena belum banyak yang membahas studi ini pada tingkat lokal. Pada penelitian ini menggunakan metode kualitatif dengan tipe penelitian deskritif. Penelitian dilakukan di Kabupaten Kotawaringin Timur dengan teknik pengumpulan data bersumber dari data primer berupa wawancara mendalam dengan Kepala Satuan Reserse Narkoba dan Sekretariat Badan Narkotika Kabupaten, kemudian data sekunder berupa laporan resmi dan artikel ilmiah. Teknik analisis data yang digunakan dalam penelitian yaitu reduksi data, penyajian data, dan menarik kesimpulan. Hasil penelitian menunjukan adanya upaya peningkatan kapabilitas namun masih belum berjalan dengan optimal. Elemen thinking ahead dan thinking again perlu mendapatkan perhatian lebih. Kendala yang dihadapi yaitu kurangnya sumber daya manusia dan anggaran, peran antar instansi tidak terkoordinasi dengan terstruktur, selain itu tidak adanya instansi definitif yaitu Badan Narkotika Nasional Kabupaten juga memiliki pengaruh besar dalam pelaksanaan operasional. Adapun, elemen thinking across sudah dapat dipahami oleh jajaran pemerintah daerah dengan adanya upaya untuk studi banding.